Fabrication of Rosuvastatin-Incorporated Polycaprolactone -Gelatin Scaffold for Bone Repair: A Preliminary In Vitro Study - Maliheh Gharibshahian; Morteza Alizadeh; Mohammad Kamalabadi Farahani; Majid Salehi (Cell Journal, 2024)
Objective: Rosuvastatin (RSV) is a hydrophilic, effective statin with a long half-life that stimulates bone regeneration.The present study aims to develop a new scaffold and controlled release system for RSV with favourable properties forbone tissue engineering (BTE).Materials and Methods: In this experimental study, high porous polycaprolactone (PCL)-gelatin scaffolds that containeddifferent concentrations of RSV (0 mg/10 ml, 0.1 mg/10 ml, 0.5 mg/10 ml, 2.5 mg/10 ml, 12.5 mg/10 ml, and 62.5 mg/10ml) were fabricated by the thermally-induced phase separation (TIPS) method. Mechanical and biological properties ofthe scaffolds were evaluated by Fourier transform infrared spectroscopy (FTIR), scanning electron microscope (SEM),compressive strength, porosity, MTT, alkaline phosphatase (ALP) activity, water contact angle, degradation rate, pHalteration, blood clotting index (BCI), and hemocompatibility.Results: SEM analysis confirmed that the porous structure of the scaffolds contained interconnected pores. FTIRresults showed that the RSV structure was maintained during the scaffold's fabrication. RSV (up to 62.5 mg/10 ml)increased compressive strength (16.342 ± 1.79 MPa), wettability (70.2), and degradation rate of the scaffolds. Scaffoldsthat contained 2.5 mg/10 ml RSV had the best effect on the human umbilical cord mesenchymal stem cell (HUC-MSCs)survival, hemocompatibility, and BCI. As a sustained release system, only 31.68 ± 0.1% of RSV was released fromthe PCL-Gelatin-2.5 mg/10 ml RSV scaffold over 30 days. In addition, the results of ALP activity showed that RSVincreased the osteogenic differentiation potential of the scaffolds.Conclusion: PCL-Gelatin-2.5 mg/10 ml RSV scaffolds have favorable mechanical, physical, and osteogenic propertiesfor bone tissue and provide a favorable release system for RSV. They can mentioned as a a promising strategy for boneregeneration that should be further assessed in animals and clinical studies.